76.5k views
1 vote
E:f = 2:3 and f:g = 5:4 work our e:g​

User Sithsu
by
4.7k points

2 Answers

2 votes

Answer:

5/6

Explanation:

e/f = 2/3 After that e= 2f/3 f/g = 5/4 So then g= 4f/5 at last

e/g= 2f/3 / 4f/5 = 1/3 x 5/2 = 5/6

User Daralthus
by
5.7k points
4 votes

Answer:

5/6

Explanation:

e/f = 2/3

Then

e= 2f/3

f/g = 5/4

Then

g= 4f/5

So

e/g= 2f/3 / 4f/5 = 1/3 * 5/2 = 5/6

User Gaurav Roy
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.